Evaluation of feedstuffs and the metabolisable energy and amino acid requirements for maintenance and growth in ostriches (Struthio camelus) - Cilliers, S. C. (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 1994.